CHARACTERIZATION OF DRIED NOODLES FROM SEAWEED (Kappaphycus alvarezii) AS POTENTIAL SUBSTITUTE FOR WHEAT FLOUR - Afifah Nurazizatul Hasanah; Aris Munandar; Dini Surilayani; Sakinah Haryati; Rifki Prayoga Aditia; Mulkas Hadi Sumantri; Ginanjar Pratama; Bhatara Ayi Meata (Food ScienTech Journal, 2021)
Dried noodles are one of the foods favored by people in Indonesia. The main ingredient of dry noodles is wheat flour which made from milling wheat. However, we usually obtain wheat from overseas by import. Therefore, to achieve food resilience in Indonesia, it is necessary to find substitutes for local ingredients with high nutrition that can be used to make dry noodles. This research aims to investigate the characteristics of dry noodles made from Kappaphycus alvarezii seaweed flour. The method used in this study was to substitute K. alvarezii seaweed flour as much as 0, 5, 10, 15, 20, and 25% in the production of dry noodles. Analysis was carried out on its chemical composition, physical properties, and organoleptic characteristics. The results showed the best result of substitution of K. alvarezii in the 5% treatment. The chemical composition in dry noodles of this treatment showed an air content of 8.39%; ash content 3.07%; fat content 0.59%; protein content 12.43%; and 0.29% crude fiber content. Meanwhile, the results of the physical test showed7.95% cooking loss;210.5 seconds cooking time; and 89.34% water absorption. The organoleptic values obtained are color 4.60 (like); aroma 4.80 (like); texture 4.23 (like); and taste 4.20 (like).